Bringing cumulative technological culture beyond copying versus reasoning - Osiurak, François; Claidière, Nicolas; Federico, Giovanni (Trends in cognitive sciences, 2023)
The dominant view of cumulative technological culture suggests that high-fidelity transmission rests upon a high-fidelity copying ability, which allows individuals to reproduce the tool-use actions performed by others without needing to understand them (i.e., without causal reasoning). The opposition between copying versus reasoning is well accepted but with little supporting evidence. In this article, we investigate this distinction by examining the cognitive science literature on tool use. Evidence indicates that the ability to reproduce others’ tool-use actions requires causal understanding, which questions the copying versus reasoning distinction and the cognitive reality of the so-called copying ability. We conclude that new insights might be gained by considering causal understanding as a key driver of cumulative technological culture. Cumulative technological culture, which describes the increase in the efficiency and complexity of tools and techniques over generations, is at the root of the evolution of human technology and is considered one of the most important scientific topics of our time.High-fidelity transmission is commonly thought to be the key driver of cumulative technological culture. The cultural niche hypothesis assumes that this transmission rests upon copying abilities, which allow individuals to reproduce others’ tool-use actions without the need of understanding them.We investigate whether the opposition between copying versus understanding possesses a cognitive reality by examining the cognitive science literature on tool use.Evidence suggests that the ability to reproduce others’ tool-use actions requires causal understanding, which challenges the validity of the copying hypothesis.